Study of spirometry parameters in suspected asthmatic children in a tertiary care hospital - Mishra, Arpita; Ugra, Deepak; Kumar, Utpal (International Journal of Contemporary Pediatrics, 2020)
Background: Asthma in children is difficult to diagnose due to inability of young children to successfully perform spirometry. However some parameters in the spirometry which are relatively effort independent can be very helpful in confirming the diagnosis of asthma. This study was conducted to find out the most commonly affected spirometry parameter in the suspected cases of childhood asthma. Methods: Total 56 children were studied between 7 to 18 years who came for outpatient visit or admitted in the paediatric ward and were clinically suspected to be asthmatic based on asthma predictive index. They were subjected to spirometry in our institute. Baseline and post bronchodilator values of spirometry parameters were studied and analysed using standard statistical tests. Results: Baseline Forced expiratory flow between 25% and 75% of vital capacity (FEF25-75%) was found to be the most commonly affected spirometry parameter in confirming the diagnosis of suspected asthmatics and correlated with the clinical diagnosis of childhood asthma. Conclusions: FEF25-75% can aid in confirming the diagnosis of suspected asthmatic children who are otherwise not treated as asthmatics and remain undiagnosed in view of not meeting the established spirometry criteria for asthma due to poor performance and ignorance of looking at this important and effort independent parameter.